Accounting for changes in the homeownership rate - Matthew Chambers; Carlos Garriga; Don E. Schlagenhauf (Federal Reserve Bank of Atlanta, 2007)
After three decades of being relatively constant, the homeownership rate increased over the 1994-2005 period to attain record highs. The objective of this paper is to account for the observed boom in ownership by examining the role played by changes in demographic factors and innovations in the mortgage market that lessened down payment requirements. To measure the aggregate and distributional impact of these factors, we construct a quantitative general equilibrium overlapping-generation model with housing. We find that the long-run importance of the introduction of new mortgage products for the aggregate homeownership rate ranges from 56 percent to 70 percent. Demographic factors account for between 16 percent and 31 percent of the change. Transitional analysis suggests that demographic factors play a more important but not dominant role farther from the long-run equilibrium. From a distributional perspective, mortgage market innovations have a larger impact on participation rate changes of younger households, and demographic factors seem to be the key to understanding the participation rate changes of older households. Our analysis suggests that the key to understanding the increase in the homeownership rate is the expansion of the set of mortgage contracts. We test the robustness of this result by considering changes in mortgage financing after World War II. We find that the introduction of the conventional fixed-rate mortgage, which replaced balloon contracts, accounts for at least 50 percent of the observed increase in homeownership during that period.
Keywords: E0; D58; D91; R21; 330; macroeconomics; housing; Wohneigentum; Wohnimmobilien; Besitzformwahl; Hypothek; Finanzinnovation; USA